Branding Politics in Pakistan: An analysis from the perspective of Political Marketing - Saima Kausar; Riaz, Saqib (Journal of Peace, Development and Communication, 2022)
The politics in Pakistan is varying from conventional to political marketing. The political parties are strategizing political campaigns similar to brands. This article reviewing the politics in Pakistan from the perspective political marketing literature. For this purpose, an extensive review on politics from the view of politics marketing in Pakistan is carried out. The literature is selected for study with the key word“political marketing in Pakistan” in google scholar through set the search category year 2012 to 2021. All the articles appear in the search related to politics of Pakistan is part of this study. Brand equity pyramid of Keller (2001) is the conceptual frame work for this study. The findings of study reveal that Pakistani politics is evolving and turning into more scientific parameters of political marketing. Political parties are emphasizing on the political identity, meaning, responses and relationship. Political parties are significantly employing the strategies of political marketing which are resonance, party image and party performance and it connects with voters through strong communication strategies. Consistent awareness about party manifestoes, confronting on opponents through propaganda techniques and symbolic connection through slogans, party anthem, and association of voters with their social and economic issues and charisma of party leader are the core components of political marketing that political parties comprise in their political marketing strategies.